Transfer of Training in Indonesia State-Owned Entreprises to Face the Asean Economic Community 2015 - Surachman Surjaatmadja (The Winners, 2014)
The purpose of this paper is to provide an overview of the theoretical importance of transfer of training for State-owned Enterprises (SOEs) in Indonesia in order to face the ASEAN Economic Community 2015. This paper is a pre-research paper for the influence of transfer of training towards firm performance. It applied a library research with secondary data analyzing literature about transfer of training and Gagné’s five learned capabilities. The expected result was the existence of a specific training system for SOEs in Indonesia for there are very diverse areas of state-owned enterprises in Indonesia. The end goal is Indonesia State-Owned Enterprises have better competitiveness in global market.